Encapsulation of Sulfur into N‐Doped Porous Carbon Cages by a Facile, Template‐Free Method for Stable Lithium‐Sulfur Cathode. Issue 39 (28th August 2020) - Zeng, Shuaibo; Arumugam, Gowri Manohari; Liu, Xianhu; Yang, Yuzhao; Li, Xin; Zhong, Hai; Guo, Fei; Mai, Yaohua
Abstract: Lithium‐sulfur (Li‐S) batteries with a high energy density and long lifespan are considered as promising candidates for next‐generation electrochemical energy‐storage devices. However, the sluggish redox kinetics of electrochemistry and high solubility of polysulfide during cycling render insufficient sulfur utilization and poor cycling stability. Herein, a facile, template‐free procedure based on controlled pyrolysis of polydopamine vesicles is described to prepare N‐doped porous carbon cages (NHSC) as a new sulfur host, which significantly improves both the sulfur utilization and cycling stability. As NHSC shows a high pore volume, continuous electron and ion transport paths, and good catalytic activity, encapsulation of S nanoparticles into NHSC endows the resulting S@NHSC electrode with a good energy storage capacity and exceptionally high electrochemical stability. Consequently, a Li‐S cell with the S@NHSC as the cathode achieves a high initial capacity of 1280.7 mAh g −1, and cycling stability over 500 cycles with the capacity decay as low as 0.0373% per cycle. Abstract : N‐doped hollow spherical carbon (NHSC) is employed as an efficient sulfur host. The conductivity of the S@NHSC composites is significantly improved, which is thanks to the continuous electronic transmission path constructed by NHSC. The shuttle effect could be suppressed effectively by the closed space inside NHSC and good catalytic activity of N‐doping, which significantly improves the electrochemical stability of Li‐S batteries.